Pengaruh Bioaktivator dan Lama Fermentasi Terhadap pH dan Kadar Nitrogen dari Kompos Kulit Ari Biji Coklat - Ruka Yulia; Mahfudhlazi Al ‘Amani; Irmayanti Irmayanti; Juliani Juliani (Fakultas Teknik, 2023)
AbstractThe epidermis of cocoa beans is one of the agricultural wastes that has not been utilized optimally. Composting from cocoa bean husks is a way of processing plantation waste that has economic value. The purpose of this study was to determine the effect of EM4 and PROMI bioactivators and fermentation time on pH and nitrogen content of cocoa husk compost. The research method used is descriptive method with 2 treatments and 3 repetitions. The treatment used was a type of bioactivator namely EM4 and promi and the duration of fermentation was 5, 10 and 15 days. The results showed that the best pH was obtained by adding EM4 bioactivator with 5 days of fermentation, namely 6.75. While the highest nitrogen content was obtained by adding EM4 with a fermentation time of 15 days, namely 1.84% for the two bioactivators.Keywords: bark, cocoa beans, compost, em4, promi